The first Myrmecotypus O. P.-Cambridge (Araneae: Corinnidae) from Argentina: description of Myrmecotypus iguazu new species - Rubio, Gonzalo Daniel (2009)
The Castianeirinae genus Myrmecotypus was described by O. Pickard-Cambridge (1894) and currently includes eight species. All of them, except the atypical M. lineatus (Emerton 1909) (only record from USA), occur in the Neotropical region (known from Mexico to Panamá), Panamá being the southern most representative distribution of genus. Reiskind (1969) carried out the revision of the subfamily Castianeirinae Reiskind 1969 from North and Central America, concluding that much more study of more extensive collections will be needed to clarify the origin and distribution of South American species of this subfamily. The influence of selection for ant-mimicry still poses many difficulties in the classification of the spider taxa involved (Reiskind 1966; 1977). Ant-mimicry implies an extreme specialization that leads in many cases to well defined, easily identifiable genera, e.g. Myrmecium Latreille 1824 and Sphecotypus O.P.-Cambridge 1895; in other cases, the selection for mimicry results in a morphological convergence that makes the separation difficult, either in genera Myrmecotypus and Apochinomma Pavesi 1881, both extremely similar but the latter of African origin, and it is not known with certainty if it really occurs in Neotropical areas (Candiani pers. comm.). Nevertheless, some characters exist that can be useful diagnoses. The genus Myrmecotypus has been retained on the ground that the posterior row of eyes is only slightly wider than the anterior and almost straight; the posterior median eyes are further from each other than from the lateral eyes, and the anterior medians are much larger than the anterior lateral; the thoracic groove is absent, with a slight depression instead; moreover, the abdomen of Myrmecotypus is only very slightly petiolated (Cambridge 1897–1905). The present work enhances the geographical distribution of Myrmecotypus, describing a new species from Argentina that represents the southernmost record of the genus so far.